On the Way to Perfection: The Characteristic of Novices of Lithuanian Jesuit Province in the 17th–18th c. - Zorkienė, Brigita (Lietuvos istorijos studijos, 2019)
This article presents the first stage of a long-lasting Jesuit formation – the Novitiate. The activities, rules, calendar, and instructions of the Jesuit Novitiates were defined by the official documents of Jesuit Order. The Novitiate in Vilnius was the only institution of its kind in the Lithuanian Jesuit Province. After the establishment of the Jesuit Novitiate in 1604, 23 people joined it, and this number gradually increased. The average number of novices in Vilnius in 1604–1771 was 56. Young people of all ages expressed their desire to join the Jesuit Order. They were admitted to the Order at the age averaging between 17–18 years, but there were also novices who did not match this average (the age of novices ranges from 15 to 30 years). Meanwhile, lower requirements for brothers made it possible for them to join the Order at an older age, with the average age of 25. Sometimes, those who had been admitted to the Novitiate had already received an education (often in Jesuit schools) or were already priests. After the establishment of the Novitiate, besides Lithuanians, another large part of the novices was from Polish lands and Ruthenians. By separating the Jesuit Provinces of Lithuania and Mazovia, the Lithuanian Province became even more “Lithuanian.” In 1604–1771, only 48 people left the Novitiate, which is only about 10 percent of the total number of the retired members in the Province (the vast majority, almost 80 percent, of the members who were retired from the Order were scholastics). This initial analysis assumes that the typical Jesuit novice is about 18-years-old and of Ruthenian or Lithuanian/Samogitian origin.